The halal awareness and halal labels: do they determine purchase intention? (study on SME’s business practitioners in Gresik) - Kholis Amalia Nofianti; Siti Nur Indah Rofiqoh (Universitas Airlangga, 2019)
This study aims to determine the relationship between halal awareness and halal labels certification on product purchase interest on Small and Medium Enterprises (SME’s) Business Practitioners in Gresik. Data collection is done by using a questionnaire filled by 52 respondents selected by purposive sampling method. All statistical analysis carried out with SPSS 22. The causative relationship between each independent variable, namely halal awareness and halal label on the dependent variable, namely purchase interest is determined by multiple linear regression. The simultaneous link between all variables on purchase intention is obtained significant results. The parsial test concludes that there was an influence of halal awareness on halal labels.On the parsial analysis of halal awareness and halal labels had a positive significant effect on purchase interest.